The Use of Computational Approaches in the Discovery and Mechanism Study of Opioid Analgesics - Zhao, Bangyi; Li, Wei; Sun, Lijie; Fu, Wei (Frontiers in Chemistry, 2020)
Opioid receptors that belong to class A G protein-coupled receptors (GPCRs) are vital in pain control. In the past few years, published high-resolution crystal structures of opioid receptor laid a solid basis for both experimental and computational studies. Computer-aided drug design (CADD) has been established as a powerful tool for discovering novel lead compounds and for understanding activation mechanism of target receptors. Herein, we reviewed the computational-guided studies on opioid receptors for the discovery of new analgesics, the structural basis of receptor subtype selectivity, agonist interaction mechanism, and biased signaling mechanism.